Effect of bed shrinkage on iron ore sintering process - Jiarui Xu; Xiaohui Zhang; Shan Qing (AIP Advances, 2022)
There exist complex chemical reactions and phase transition processes—melting and solidification—in the iron ore sintering process. This will result in bed shrinkage and has an important impact on the sintering process and sinter properties. Numerical simulation was carried out in this paper, and it is based on the porous medium and double-energy equation model, coupled with the porosity shrinkage model. The influence of bed shrinkage on the sintering process was explored and revealed by comparing the calculation results, considering and neglecting bed shrinkage. The results indicate that bed shrinkage has less influence on the highest temperature in the area above 0.15 m of the sintered bed but it severely decreases by about 60 K below 0.15 m. Bed shrinkage makes the thickness of the combustion zone reduce by about 1.367, 1.398, and 4.367 cm at 500, 1000, and 1500 s, respectively. Bed shrinkage reduces the vertical sintering velocity, and the highest temperature of flue gas decreased by 77 K approximately; in addition, it also has a delay of 50 s to reach the highest temperature. The volume concentration of SO2 in the flue gas remains unchanged considering bed shrinkage, but it has a delay of about 50 s to reach the maximum value.